The EC budget and agricultural policy reforms, with special reference to cereals - Ackrill, Robert (1992)
The aim of this thesis is to explore the links that exist between the Common Agricultural Policy (CAP) of the European Communities (EC) and the EC budget. In particular, the thesis examines the impact on the budget of reforming the CAP. It shows that the nature of support offered under the CAP up to the 1992 MacSharry reforms has a strong historical precedent in French and German history. It then goes on to examine in greater detail the support mechanisms of the cereals and oilseeds sectors. The cereals sector is focused on because of its importance in agricultural output and in total agricultural support expenditure by the EC. Oilseeds is considered for its policy linkages with cereals in both production and consumption. The detailed nature of expenditures on these sectors is examined in detail, with particular emphasis placed on costs and policy problems arising out of intervention storage.